Recent progress in hormone research : the proceedings of the Laurentian Hormone Conference. - Pincus, Gregory, 1903-1967 (Academic Press, Inc., Publishers, 1950)
Recent Progress in Hormone Research: The Proceedings of the Laurentian Hormone Conference, Volume 5 presents the proceedings of the sixth annual meeting of the Laurentian Hormone Conference held on September 1949 at Franconia, New Hampshire. The book presents articles on humoral mediators in nervous transmission; ovarian physiology and function; and pituitary physiology and functions. The text also includes articles on the chemistry and physiology of the sex hormones; hormones and tumors; and the mechanisms of hormone action. Endocrinologists, oncologists, and other scientists involved in hor.